Differences in The Effectiveness of Dry and Wet Cupping to Reduce Dysmenorrhea among Teenager at Ngemplak Sleman Yogyakarta - Asmarani, Fajarina Lathu; Fatmasari, Sindi Fazri; Lestiawati , Endang (proceedinginternational, 2023)
The prevalence of dysmenorrhea worldwide ranges from 15.8 to 89.5% and Indonesia was 64.25%. Dysmenorrhea was experienced by young women aged 18 to 24. The teenagers at Wedomartani, Ngemplak, Sleman, Yogyakarta reported that they experienced dysmenorrhea at 18 to 20 years old. Dysmenorrhea might affect daily activities. Pain can be managed using non-pharmacological methods such as dry and wet cupping therapies. The goal of this study is to find out the differences in the effectiveness of dry and wet cupping to reduce dysmenorrhea among teenagers at Wedomartai, Ngemplak, Sleman, Yogyakarta. This is quantitative quasi- experimental research with a pretest-posttest without control group design. This research used a random sampling technique. thirty teenagers became respondents. The research instruments were questionnaires, a numerical scale, a cupping set, and observation sheets. Data were analyzed using the paired t-test and independent t-test. The paired t-test on dry cupping therapy showed a p-value of 0.000. The pretest score was 4.67 then the post-test was 2.93. The analysis of wet cupping therapy showed a p-value of 0.000. A decrease in dysmenorrhea can be seen at the pretest score of 5.53 and the posttest of 3.20. The independent t-test showed a p-value of 0.704 after receiving dry and wet cupping therapies. So we can dry and wet cupping therapy is equally effective in reducing dysmenorrhea pain in adolescents in Wedomartai, Ngemplak, Sleman, Yogyakarta dan Wet cupping is more effective than dry cupping. Teenagers can use wet cupping to relieve menstrual pain.